POSSIBLE ROUTES OF APPROACHING OF SERBIA (AGRO INDUSTRIAL COMPLEX) TO THE EU AND THE WTO - Kuzman, Boris; Tešić, Aleksandra; Đelić, Anastazija Tanja (Economics of Agriculture, 2013)
The priority aim of the Republic of Serbia in the framework of "CEFTA", in addition to striving to become a member of the WTO should be the aspiration to full membership in the European Union. Accession to the WTO countries is, in effect, to give up a degree of national sovereignty. Benefits of harmonizing the legal framework for the country which are CEFTA signatories mainly depend on their business - export structure and the degree of liberalization of regulations in key sectors compatible with WTO provisions. It envisions the transformation of customs duties and non-tariff protection measures through the so-called tariffication - calculating the average ratio of selective domestic and international (import) prices of agricultural products during the reference period. To survive in conditions of excessive global supply of agricultural products moderate zone, which is based on the high direct and indirect care, Serbia should conduct an active policy of subsidizing domestic agricultural production, exports and imports to protect domestic production in accordance with the terms and conditions of the world market, WTO and the European Union in the framework of CEFTA.